The complete chloroplast genome of a new candidate cultivar, Sang Jae, of Abeliophyllum distichum Nakai (Oleaceae): initial step of A. distichum intraspecies variations atlas. Issue 2 (3rd July 2019) - Min, Juhyeon; Kim, Yongsung; Xi, Hong; Jang, Taewon; Kim, Gwanho; Park, Jongsun; Park, Jae-Ho
Abstract: Chloroplast genome of Sang Jae, new candidate cultivar of Abeliophyllum distichum Nakai, has been sequenced to reveal infraspecific relationship of wildtypes and cultivars. Its length is 156, 008 bp long (GC ratio is 37.8%) and has four subregions: 86, 773 bp of large single copy (35.8%) and 17, 827 bp of small single copy (31.9%) regions are separated by 25, 704 bp of inverted repeat (43.2%) regions including 133 genes (87 protein-coding genes, eight rRNAs, and 37 tRNAs). Phylogenetic trees show that A. distichum is clustered with twelve Forsythia species and intraspecies variations level is similar to Olea europaea .